2017
DOI: 10.20471/acc.2017.56.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ganglion Cell Complex and Retinal Nerve Fiber Layer Thickness in Glaucoma Diagnosis

Abstract: The aim was to compare retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) thicknesses in patients with primary open angle glaucoma (POAG), ocular hypertension (OH) and healthy subjects, and to investigate the role of GCC parameters in glaucoma diagnosis. Eighty-one patients were divided into four groups according to Hodapp-Parrish-Anderson classification: 26 OH, 22 early POAG, 10 moderate to advanced POAG, and 23 healthy subjects. All patients underwent RNFL and GCC thickness measurement using SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
5
3
Order By: Relevance
“…GCL parameters however perform poorly in differentiating glaucomatous from non-glaucomatous eyes and between normal and PPG in our cohort of patients. This is in contrast with previous studies which reported that GCL parameters have a better diagnostic ability compared to RNFL parameters [27] . Nevertheless, there were an abundant body of evidence reporting otherwise, agreeing with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…GCL parameters however perform poorly in differentiating glaucomatous from non-glaucomatous eyes and between normal and PPG in our cohort of patients. This is in contrast with previous studies which reported that GCL parameters have a better diagnostic ability compared to RNFL parameters [27] . Nevertheless, there were an abundant body of evidence reporting otherwise, agreeing with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, overall GCC thickness in the control group was measured as 111.3 µm, which was higher than a previous study by Aydogan et al (100.7 µm) 21 ; however, it was found lower than the value found in Vidas et al's study (119.61 µm). 22 Thus, the overall GCC thickness was 104.67 µm in the present study, which was in the middle of the values found by Aydogan et al (100.5 µm) 21 and Vidas et al (112.58 µm) study 22 in the glaucoma suspect group. In overall GCC thickness, age-related decay was present in both control (0.23 µm) and glaucoma suspect (0.11 µm) groups; however, these decays between groups were not found to be statistically significant.…”
Section: Discussioncontrasting
confidence: 47%
“…Across all key questions, 83 studies (reported in 96 publications, total 75 887 participants) were included (30 trials and 53 diagnostic accuracy studies) (Figure 2). Sixteen studies were carried forward from the 2013 reviews, and 67 studies were new.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three studies evaluated the diagnostic accuracy of screening tests (reported in 59 publications, n = 65 464) (eTables 3-4 in the Supplement). Most studies evaluated spectral-domain OCT (29 studies, n = 11 434), tonometry (17 studies, n = 49 742), and visual field assessment (10 studies, n = 11 633). No study evaluated the diagnostic accuracy of a comprehensive ophthalmological examination.…”
Section: Resultsmentioning
confidence: 99%